Medical Students Perception about Doctor's Body Image Using Stunkard Figure Rating Scale (FRS) Method - Agustina Arundina Triharja Tejoyuwono; Muhammad Riedha (International Journal of Public Health Science (IJPHS), 2015)
Doctor as health workers are obliged to be role models, especially in healthy and active life stlyle projected as having an ideal body image. It beneficial to increase self confidence, improve sucess in counceling and health service satisfaction and as well as gaining patient’s trust. Body image sometimes considered unnecessary, however it could be quite disturbing in health service.Therefore, this study aims to describe medical student’s perception on doctor’s body images as health workers in Tanjungpura University. This resarch used survey in descriptive study with quantitative data. The subject was medical students from medical, pharmacy and nursing grade 2011 to 2014. Triangulation data collected from doctor working in medical school, and Tanjungpura University Hospital. Sample was choosen by purposive sampling and analyzed by descriptive statistic. This research had been approved by medical faculty ethic research admission at Untan no. 3986/UN22.9/DT/2014. A total of 576 medical students were enrolled in this research. 93.06% stated that body image is important for doctor and it will influence the theraphy. 67.2% chose picture 4 (normal nutritional status) in Stunkard Figure Rating Scales the ideal body images for doctors. Nevertheless,17.01% chose picture < 3 (underweight) and 15.8% choose picture > 5 (overweight and obesity) as the doctor’s ideal body images. Doctors that work in Educational field were the most important field that needs a good body image (42.88%0, followed by doctor in hospital (24.83%). Based on triangulation data from 16 medical school doctors, and 7 Tanjungpura University Hospital doctors, suggested that body image will not impact the therapy (82.6%) and the most important field that needs ideal body images was in hospital (43.5%). Body image is very important and it will influence doctor theraphy. Doctor in educational field should have a ideal body image with normal nutrition status.